Substratum choice for nesting in male Nile tilapia Oreochromis niloticus - Mendonca, F. Z. [UNESP]; Volpato, G. L. [UNESP]; Costa-Ferreira, R. S. [UNESP]; Goncalves-de-Freitas, E. [UNESP] (Wiley-Blackwell, 2010)
Four substrata were offered to groups of adult Nile tilapia Oreochromis niloticus (one male and two females) simultaneously: pure sand, a mixture of sand and shells, stones and no substratum. The results showed that males chose to dig nests in a lighter and more homogeneous substratum.
Keywords: choice test; cichlid; nest; welfare